Investigation of anthropometric and work-rate profiles of elite South American international soccer players - Rienzi, E.; Drust, B.; Reilly, T.; Carter, J. E.; Martin, A. (The Journal of Sports Medicine and Physical Fitness, 2000)
The aim of the current investigation was to determine the movement profiles of elite South American soccer players during international competition and examine the relationship between anthropometric profile and work-rate variables. METHODS: Seventeen full-time professional soccer players were filmed while competing for their countries. Anthropometric profiles were obtained for eleven of these players. Six full-time professional players from the English Premier League were also filmed for comparative purposes. RESULTS: The South American international players covered significantly less (p<0.05) total distance during match-play than English Premier League players (International, 8638+/-1158 m; English Premier League, 10104+/-703 m). The total distance covered during the second half of the game was significantly reduced (p<0.05) compared to the first half distance for both groups of players (mean+/-SD first half 4605+/-625 m; mean+/-SD second half 4415+/-634 m). The data for both groups of players were combined to evaluate positional differences in the workrate profile. Midfield players covered a significantly greater (p<0.05) distance than forward players (midfield, 9826+/-1031 m; forwards, 7736+/-929 m) and defenders covered a greater (p<0.05) distance jogging backwards than forward players (defenders, 276+/-155 m; forwards, 68+/-25 m). Forwards sprinted a greater distance (p<0.05) than defensive players (defenders, 231+/-142 m; forwards, 557+/-142 m). Mean somatotype was a balanced mesomorph (2-5 1/2-2). Body mass and muscle mass was related to the total distance covered (r=0.43, r=0.53, p<0.05). CONCLUSIONS: Based on these data, it seems that an individual's work-rate profile is dependent upon the type of competition and the playing position. Relationships between anthropometric profile and work-rate are complex due to the interaction between the variables that determine work-rate.